Improving Students’ Speaking Skills Through A One-Hour Daily English Learning Routine - Rini Kesuma Siregar; Dina Syahfitri Siregar (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2026)
The "Theories and Practice of Translation" course is a foundational component of the English Education program designed to equip students with both theoretical frameworks and practical competencies. However, students frequently struggle to apply theoretical principles consistently during the translation process. This study analyzes the application of translation theories among undergraduate students at Universitas Graha Nusantara. Employing a qualitative descriptive approach, the research involved students from the English Education Study Program who had completed the course. Data were gathered through an analysis of translation assignments, classroom observations, and semi-structured interviews. The findings reveal that while students utilized theories such as equivalence, semantic and communicative translation, and functional approaches, their application remained inconsistent. Many participants tended to rely on intuition when encountering complex linguistic problems. Nevertheless, the results indicate that guided practice and reflective discussions significantly enhanced students' theoretical awareness and translation quality. This study concludes that the continuous integration of theory into practical activities is essential for developing the analytical skills necessary to achieve professional translation competence.